Can we design spontaneity? The tension between evolution and design and the defense of liberalism in Hayek - Nathanaël Colin-Jaege (Duke University, Center for the History of Political Economy (CHOPE), 2021)
F.A Hayek is one of the most important and influential advocates of liberalism in the 20th century. His theory is famously based on the concept of spontaneous order, an order emerging from the interaction of individuals without central control and appears critical of every form of interventionism. At the same time Hayek also defends the necessity to improve or even to constitute a liberal order. This seminal tension, between an evolutionary strand and a designing strand in Hayek's political theory, gave birth to a set of debates regarding the consistency of Hayek's thinking. In this article I argue, against several commentators and critics, that the theory of spontaneous order, which draws on complexity theory and cultural evolution, does not clash with Hayek's defense of liberalism, but allow for a better understanding of it. My analysis puts forward the importance of a liberal design of a framework enhancing spontaneity, a radical liberalism, which goes beyond a whiggish liberalism defending the slow piecemeal evolution of social norms and institutions. I thus defend that Hayek provides a theory of a liberal design of spontaneity. Since Hayek is concerned by the liberal framework allowing for the growth of a beneficial spontaneous order, his liberalism should not be defended on evolutionary grounds, which are flawed, but on normative grounds, which are debatable.
Keywords: B25; B31; B41; B53; 330; Hayek; Liberalism; Spontaneous order; Complexity; Cultural Evolution